Peningkatan Literasi Digital Guru Sekolah Dasar Dalam Menghadapi Pembelajaran Daring - Ade Rizki Rinaldi; Agus Bahtiar; Arga Esa Putra; Arunika Wijaya (CV. Multi Kreasi Media, 2023)
This Community Service Program aims to improve digital literacy for elementary school teachers in facing the challenges of online learning in the digital era. The rapid development of information and communication technology has brought significant changes to learning methods, including demands for teachers to master various digital platforms. However, in reality, many elementary school teachers still face limitations in using technology, both in terms of skills, access to devices, and strategies for delivering learning materials online. This program was implemented through a series of activities, including training, workshops, mentoring, and evaluation. The training materials focused on the use of online learning platforms such as Google Classroom, Zoom, Canva, and the creation of engaging and interactive digital learning materials. In addition, participants received guidance in overcoming technical obstacles and strategies for building effective communication with students in online learning. The results of this program showed a significant improvement in teachers' understanding and skills in operating educational technology. Teachers became more confident in designing and delivering digital-based learning, online classroom management improved, and student participation in the learning process increased. The outputs of this activity included a digital literacy guide module, tutorial videos on the use of online learning platforms, program activity reports, and the establishment of a knowledge-sharing community among teachers. This program is expected to support the transformation of technology-based education, improve the quality of online learning, and create educators who are more adaptive and creative in facing future technological developments.